Association between inflammatory bowel disease and Parkinson’s disease: a prospective cohort study of 468,556 UK biobank participants - Wang, Hai-li; Wang, Zhi-yun; Tian, Jie; Ma, Dong-rui; Shi, Chang-he (Frontiers in Aging Neuroscience, 2024)
Introduction: Inflammatory Bowel Disease (IBD) and Parkinson's disease (PD) are both chronic, progressive disorders. As such, given the inconclusive results of extensive research on the association between IBD and PD, our study intends to examine this relationship further using the UK Biobank database. Methods: We conducted a prospective cohort study using the Cox proportional hazards model, analysing data from the UK Biobank to investigate the relationship between IBD and PD, following subjects until PD diagnosis, loss to follow up, death or study termination on 30 June, 2023. Results: The results show that IBD had no effect on the risk of PD (HR: 1.356, 95%CI: 0.941–1.955, P = 0.103), and the effect remained consistent in specific Crohn’s disease, ulcerative colitis or unclassified IBD populations. In addition, after sensitivity analysis using propensity matching scores and excluding patients diagnosed with PD 5 or 10 years after baseline, IBD had no effect on the risk of PD. However, in the subgroup analysis, we found that in females (HR: 1.989, 95%CI: 1.032–3.835, P = 0.040), the polygenic risk score was highest (HR: 2.476, 95%CI: 1.401–4.374, P = 0.002), and having ulcerative colitis without hypertension (HR: 2.042, 95%CI: 1.128–3.697, P = 0.018) was associated with an increased risk of PD. Conclusions: In conclusion, over an average follow-up period of 13.93 years, we found no significant association between IBD and PD.